Optimalisasi Pelaksanaan Proyek Pembangunan Rumah sakit Gunadarma Medika dengan Metode CPM dan PERT - Prabowo Angga Sujarno; Esa Julian Firdaus; Sutrisno Sutrisno (Fakultas Teknik, 2023)
Projects, of course, cannot be separated from the time factor. By reducing the time the project will run more efficient and of course will reduce the set duration. CPM is one method that can reduce the total time of the project executed by determining the critical path. In this case, we discuss the Gunadarma Medika hospital and the Gunadarma University creative industry center building. The data needed in this study include the activities that occur, the duration of the activity and the schedule for carrying out the activity. The data obtained will be re-processed into a Net Work Diagram to describe the relationship between activities and the critical path.